Diabetes Mellitus Type 1 During COVID-19: Psychological Symptoms and Eating Attitudes - Benioudakis, Emmanouil S.; Karlafti, Eleni; Georgiou, Evangelos D.; Kalaitzaki, Argyroula; Kaiafa, Georgia; Savopoulos, Christos; Didangelos, Triantafyllos (Current Diabetes Reviews, 2023)
Background: Diabetes Mellitus Type 1 is a chronic metabolic disorder, the treatment of which extremely burdens the patient. The lockdown, as a measure to prevent the spreading of the 2019 coronavirus disease, was a major challenge for the general public. People with chronic diseases, such as T1D patients, have complex emotional and psychological needs and are at increased risk for both depressive symptoms and anxiety. Objective: The aim of this study was to evaluate the impact of body mass index of T1D patients on the psychological symptoms and eating habits, as well as the prognostic factors of the psychological symptoms during the lockdown period. Methods: Diabetes mellitus patients were invited to complete this survey from the outpatient Diabetes clinic of the General Hospital of Chania and the “AHEPA” General University Hospital of Thessaloniki in Greece. Psychological symptoms were assessed using the DASS-42 questionnaire, and eating habits were assessed using the EAT-26 questionnaire. Results: Overall, 112 T1D patients were analyzed (response rate: 28.8%). Obese T1D patients appear to be at greater risk of developing psychological symptoms, such as depression, anxiety, and stress. Furthermore, disordered eating behaviors and bulimia and food preoccupation subscale are associated with psychological symptoms. Conclusion: The findings suggest that obese T1D patients are at greater risk of developing psychological symptoms. Moreover, when an eating disorder is triggered, negative psychological symptoms such as depression and anxiety are reduced. The results of this study may guide targeted interventions among T1D patients.
Keywords: obesity